UJI EFEKTIVITAS MIMBA (Azadirachta indica A. Juss) DAN PEMBERIAN NITROGEN TERHADAP PELINDIAN NITROGEN DAN PERTUMBUHAN TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) PADA TANAH GAMBUT - Maynita, Sandra; Amri, Al Ichsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to find out the effectiveness of Neem and the application of Nitrogen to nitrogen leaching and sweet corn growth on peat soil. This research has been conducted in gauze house of Technical Implementation Unit (TIU) experimental station and analysis of leachate water has been conducted in Laboratory of Soil Science, Faculty of Agriculture, University of Riau, Pekanbaru. The research was held from October 2014 until January 2015. This research is factorial experiment and prepared in Completely Randomized Design (CRD) that consisted of 2 factors, which are nitrogen (N) application which is without nitrogen and with nitrogen 3,75g/column, and the second factor is Neem (M), which is without neem, 0,37g/column, 0,56g/column, 0,75g/column. The data that were obtained from research results were analyze statistically by analysis of variance (ANOVA). The result of ANOVA further were tested using Duncanâs multiple range test 5% significant level. The results of this research show that the application of neem until 0,75g/column dosage is not effective in decreasing nitrogen leaching on peat soil. The application of nitrogen on peat soil increases ammonium on leachate water on fourth week, but not on second and sixth week, while, on nitrat of leachate is significantly different compare to without application of nitrogen. The application of neem until 0,75g/column dosage and nitrogen 3,75g/column does not increase the growth of plant. Â Keywords : Neem, Nitrogen, Nitrogen leaching, Sweet corn, Peat soil